COMPACTION BEHAVIOUR OF LATERITIC SOIL MODIFIED WITH CEMENT AND RICE HUSK ASH FOR ROAD CONSTRUCTION (Nigerian Journal of Technology, 2019)
This study is an investigation into the possibility of using rice husk ash blended with cement (C-RHA) in the modification of the basic engineering properties of a marginal lateritic soil with the aim of qualifying the soil for use in the construction of roads. In the study, the properties of the natural soil sample such as bearing strength (measured in California Bearing Ratio: CBR), compaction behaviour as well as other consistency parameters were evaluated. The same properties were also evaluated for the soil samples modified with C-RHA. The findings of the study show that an increase in values of the C-RHA results a decrease in plasticity. An improvement in the CBR was observed with increasing value of the RHA at specified cement contents with peak values at 5% cement and 10% RHA. This indicates the potential of using 7.5-10% RHA admixed with 5% cement contents for laterite soil stabilization for use as a sub-grade soil for road construction.http://dx.doi.org/10.4314/njt.v38i3.5